If your adolescent has ADHD : an essential resource for parents - Power, Thomas J.; Andrews, Linda Wasmer (Adolescent mental health initiative of the Annenberg Public Policy Center and the Sunnylands Trust., 2018)
If Your Adolescent Has ADHD: An Essential Resource for Parents provides the up-to-date information and down-to-earth support that parents need. The book is an authoritative guide to teen ADHD, including symptoms, diagnosis, treatment, school interventions, and parenting strategies. It addresses common concerns, such as driving, curfews, extracurricular activities, and homework.